A Novel Fluorescent Labeling Method Enables Monitoring of Spatio‐Temporal Dynamics of Developing Microsporidia. (16th December 2015) - Santiana, Marianita; Takvorian, Peter M.; Altan‐Bonnet, Nihal; Cali, Ann
Abstract: The microsporidium, Anncaliia algerae ( Brachiola algerae ), is a eukaryotic obligate intracellular parasite first isolated from mosquitoes and is an important opportunistic human pathogen that can cause morbidity and mortality among immune‐compromised individuals including patients with AIDS and those undergoing chemotherapy. There is little known about the Microsporidia–host cell interface in living host cells, due to current approaches being limited by the lack of fluorescent reporters for detecting the parasite lifecycle. Here, we have developed and applied novel vital fluorescent parasite labeling methodologies in conjunction with fluorescent protein‐tagged reporters to track simultaneously the dynamics of both parasite and host cell specific components, including the secretory and endocytic trafficking pathways, during the entire infection time period. We have found dramatic changes in the dynamics of host secretory trafficking organelles during the course of infection. The Golgi compartment is gradually disassembled and regenerated into mini‐Golgi structures in parallel with cellular microtubule depolymerization. Importantly, we find that Microsporidia progeny are associated with these de novo formed mini‐Golgi structures. These host structures appear to create a membrane bound niche environment for parasite development. Our studies presented here provide novel imaging tools and methodologies that will facilitate in understanding the biology of microsporidial parasites in the living host.